1998
DOI: 10.1126/science.279.5356.1547
|View full text |Cite
|
Sign up to set email alerts
|

Role of PML in Cell Growth and the Retinoic Acid Pathway

Abstract: The PML gene is fused to the retinoic acid receptor alpha (RARalpha) gene in chromosomal translocations associated with acute promyelocytic leukemia (APL). Ablation of murine PML protein by homologous recombination revealed that PML regulates hemopoietic differentiation and controls cell growth and tumorigenesis. PML function was essential for the tumor-growth-suppressive activity of retinoic acid (RA) and for its ability to induce terminal myeloid differentiation of precursor cells. PML was needed for the RA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(101 citation statements)
references
References 25 publications
(9 reference statements)
2
99
0
Order By: Relevance
“…3 Overexpression of PML inhibits cell proliferation, 4 whereas pml −/− cells grow faster than their wild-type counterparts. 5 Moreover, pml −/− cells are resistant to multiple apoptotic stimuli, for example, hydrogen peroxide (H 2 O 2 ), tumor necrosis factor- α , and ionizing radiation. 6 There are multiple PML spliced isoforms.…”
mentioning
confidence: 99%
“…3 Overexpression of PML inhibits cell proliferation, 4 whereas pml −/− cells grow faster than their wild-type counterparts. 5 Moreover, pml −/− cells are resistant to multiple apoptotic stimuli, for example, hydrogen peroxide (H 2 O 2 ), tumor necrosis factor- α , and ionizing radiation. 6 There are multiple PML spliced isoforms.…”
mentioning
confidence: 99%
“…We hypothesize that cellular intersections connecting different pathways may serve as molecular platforms for ICP0 to effectively coordinate its multiple functions. A dynamic nuclear structure, nuclear domain 10 (ND10), which has been implicated in numerous cellular processes, including gene regulation (21,22), apoptosis (23,24), DNA repair (25), oncogenesis (26,27), and antiviral defense (28), is a suitable candidate to bridge the cross talk and networking among different cell pathways.…”
mentioning
confidence: 99%
“…HDACs are one such potential candidate, as they have been shown to interact with both pRB and PML. 36,37 We don't favor this interpretation, because our previous studies have indicated that HDACcontaining complexes interact with pRB in a GST-RB pull-down assay irrespective of the growth state of the cells. 29 Based on this line of reasoning, we expect that PML-pRB interactions are likely quite direct.…”
Section: Discussionmentioning
confidence: 92%
“…33,34 Indeed, Pml −/− mice show increased susceptibility to cancer-promoting agents. 35,36 Interestingly, in a recent study by Vernier et al the authors showed that expression of PML in U2OS osteosarcoma cells results in the association of PML with E2F target genes and repression of their expression. 23 However, other studies have suggested that the formation of PML nuclear bodies is dispensable for induction of senescence, and that the individual PML proteins are key.…”
Section: Discussionmentioning
confidence: 99%